Improving Supervisory Consultant Performance in Construction Projects: Assessments in the LKPP's SIKaP Application for Enhanced Efficiency - Heston, Yudha Pracastino; Wulandari, Mariana; Fernando, Robi (Sustainable Civil Building Management and Engineering Journal, 2024)
This article focuses on enhancing the performance of supervisory consultants in construction projects through assessments conducted in the LKPP's SIKaP application. Supervision plays a crucial role in ensuring the smooth execution of construction activities and addressing potential obstacles. The quality and safety of construction operations have become increasingly important, necessitating effective supervision. The article highlights the importance of conducting assessments to measure the success of supervisory consultants in meeting project objectives and adhering to established standards. It emphasizes the evaluation of various performance criteria, including human resources, equipment, materials, costs, time, and quality. The assessment process enables the identification of strengths and weaknesses, facilitating corrective measures and improving future performance. The article also emphasizes the interconnectedness of construction supervision and project management, with project management playing a pivotal role in achieving project goals. Communication management is highlighted as a crucial aspect for effective project execution. The regulatory framework governing technical supervision activities in construction projects is discussed, along with the roles and responsibilities of construction management and construction supervision service providers. The article emphasizes the importance of on-site inspections, project administration, progress monitoring, and quality management in construction supervision. Lastly, the article discusses the evaluation of providers' performance in goods/services procurement, emphasizing the importance of quality, cost efficiency, and adherence to standards. The implementation of the SIKaP application is seen as a means to enhance transparency, accountability, and project quality in the construction industry, fostering a culture of continuous improvement and industry benchmarking.